Testing McClelland at the academy: an analysis of entrepreneurial behavioral characteristics - Mourão, Paulo (2020)
The aim of this study was to test whether Entrepreneurial Behavioral Characteristics (EBC) develop in Brazilian university students as described by McClelland. Methodological procedures tested McClelland’s (1963;1987) perspective with a sample of university students, also emphasizing the dimensions leading to sustainable businesses. Data collection was performed using a closed questionnaire with fifty-five questions using the Likert scale, applied manually for five years, at the beginning of seven different semesters. The questionnaire was answered by a sample of 238 university students from bachelor’s degrees at a Brazilian public university. Data analysis was based on exploratory factor analysis using the main component method and Varimax rotation and confirmatory factor analysis. It has been pointed out that the 10 dimensions of the EBCs are a single factor which also poses methodological challenges as a tendency of homogenization observed in the respondents, which, in itself, can be challenging for the entrepreneurship strategies expected of universities in the future.